The Role of Digital Accounting Practices in Enhancing Financial Reporting Quality of Medium-Sized Businesses - Olaoye, Ayoola Azeez; Bello, Wasiu; oladeji, Felicia Olauremilekun (Indonesian Management and Accounting Research, 2025)
The growing complexity of financial operations for medium-sized businesses (MSBs) requires innovative solutions to ensure transparency, accuracy, and efficiency in financial reporting. This study investigates the role of digital accounting practices in enhancing the financial reporting quality of medium-sized businesses, focusing on Nigerian MSBs. Integrating advanced technologies, such as artificial intelligence (AI), blockchain, and data analytics, potentially and significantly improve reporting accuracy and efficiency. Primary data were collected from 2,000 digital accountants in Nigeria using a mixed-method approach. The findings reveal that digital accounting tools, including AI and blockchain technologies, play a positive role in improving the financial reporting quality of MSBs by enhancing accuracy, transparency, and timeliness in financial transactions. This study highlights the importance of digital tools in fostering transparent and quality financial reports for MSBs. The research concludes adoption of blockchain technology and artificial intelligence enhances the quality of financial reporting in medium-sized businesses. Medium-sized business managers should consider implementing pilot programs to showcase the effectiveness of artificial intelligence and blockchain technology in real-world scenarios for accounting applications. They should also invest in comprehensive staff training and educational programs for better practice